PENGARUH PEMBERIAN PUPUK KOMPOS DAN UREA TERHADAP PERTUMBUHAN BIBIT PINANG (Areca catechu L.) - Iwan Wahyudi; Muhammad Hatta (Jurnal Floratek, 2009)
Effect of Compost and Urea on Seedling Growth of Betel Palm (Areca catechu L.) Iwan Wahyudi dan Muhammad Hatta Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT This study was aimed at finding an appropriate dosage of compost and urea for seedling growth of betel palm. In addition, this study was also to determine whether the provision of compost can increase effectiveness of urea fertilizer for seedling growth of betel palm. Results of research showed that compost significantly affected seedling growth of betel palm. The best dosage of compost for the seedling growth was 1.5 kg per seedling. Urea fertilizer also significantly affected seedling growth of betel palm. The best dosage of urea for the seedling growth was 1.5 g per seedling. There were no significant interactions in most variables of seedling growth observed.